Necking in steady-state drawing of polymer fibres - Zahorski, S. (Archives of Mechanics, 1996)
The concept of non-uniform extensional motions of materially non-uniform simple locally isotropic solids is used to discuss some general properties of fibre drawing processes. In the approach presented, axial and radial temperature and structure variations can be taken into account as some kind of non-uniformity. For steady cold-drawing processes various necking conditions are considered in general and particular cases. The effects of particular force components, i.e. inertial and rheological, are discussed in greater detail for S-shaped velocity profiles.